Rethinking cancer prevention for migrant populations in Queensland, Australia: A retrospective cohort study comparing culturally and linguistically diverse and Australian born cancer patients - Brighid Scanlon; David Wyld; Natasha Roberts; Jo Durham; Ghasem (Sam) (Taylor & Francis Group, 2023)
International evidence suggests migrants experience significant cancer inequities. In Australia, there is limited information assessing equity for Culturally and Linguistically Diverse (CALD) migrant populations, particularly in cancer prevention. Cancer inequities are often explained by individualistic, behavioural risk factors; however, scarce research has quantified or compared engagement with cancer prevention strategies. A retrospective cohort study was conducted utilising the electronic medical records at a major, quaternary hospital. Individuals were screened for inclusion in the CALD migrant or Australian born cohort. Bivariate analysis and multivariate logistic regression were used to compare the cohorts. 523 individuals were followed (22% were CALD migrants and 78% Australian born). Results displayed that CALD migrants made up a larger proportion of infection-related cancers. Compared to Australian born, CALD migrants had lower odds of having a smoking history (OR = 0.63, CI 0.401-0.972); higher odds of 'never drinking' (OR = 3.4, CI 1.473-7.905); and lower odds of having breast cancers detected via screening (OR = 6.493, CI 2.429-17.359). Findings affirm CALD migrants' low participation in screening services but refute the assertion that CALD migrants are less engaged in positive health practices, enabling cancer prevention. Future research should examine social, environmental, and institutional processes and move beyond individualistic, behavioural explanations for cancer inequities.